2017
DOI: 10.15537/smj.2017.12.20973
|View full text |Cite
|
Sign up to set email alerts
|

Salivary parameters among Arabian snuff (Shammah) users

Abstract: Objectives:To evaluate the salivary flow rate (SFR), pH, and buffer capacity (BC) among healthy shammah users (SU) in comparison with healthy non-shammah users (NSU).Methods:This case-control study was conducted at the College of Dentistry, Jazan University, Jazan, Kingdom of Saudi Arabia between March 2016 and May 2017. A sample of 27 SU and 30 NSU were recruited. Unstimulated saliva was collected and SFR, pH, and BC were determined. Dental health was assessed using the decay-missing-filled teeth (DMFT) index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The incidence rates of oral cancer in these countries for females and males were 1.8 and 2.6, respectively, per 100,000 per annum in 2015 (Ferlay et al, 2015). Chewing habits, such as chewing Shamma, tobacco, and khat are extensively used in Arabic countries (Al-Ak'hali et al, 2017). There is a strong relationship between chewing Shamma and oral cancer (Basha et al, 2019).…”
Section: Quality Assessment Of Information On Oral Cancer Provided Atmentioning
confidence: 99%
“…The incidence rates of oral cancer in these countries for females and males were 1.8 and 2.6, respectively, per 100,000 per annum in 2015 (Ferlay et al, 2015). Chewing habits, such as chewing Shamma, tobacco, and khat are extensively used in Arabic countries (Al-Ak'hali et al, 2017). There is a strong relationship between chewing Shamma and oral cancer (Basha et al, 2019).…”
Section: Quality Assessment Of Information On Oral Cancer Provided Atmentioning
confidence: 99%
“…20 , 21 This hypothesis is reinforced by several in-vitro studies reporting genotoxic and DNA-damaging effects of different smokeless tobacco products that is mediated through production of reactive oxygen species. 37 In fact, epidemiological studies have revealed higher odds of oral and upper aerodigestive tract cancers in tobacco users than in non-users. 38 In the literature, TAC is reduced among smokers.…”
Section: Discussionmentioning
confidence: 99%